On the location of different titanium sites in Ti-OMS-2 and their catalytic role in oxidation of styrene - Hadi Nur, Hadi Nur (Elsevier B.V., 2007)
Octahedral manganese oxide molecular sieves (OMS-2) modified by impregnation of TiO2 exhibit a higher catalytic activity for oxidation of styrene with tert-butylhydroperoxide in comparison to titanium-incorporated OMS-2, where the styrene conversions were ca. 70% and 45-50%, respectively. The framework of titanium species has no effect on the enhancement of catalytic activity, while the nonframework of titanium species induces a synergetic effect that enhances the oxidation of styrene with tert-butylhydroperoxide